Nigerian public administrators' perception of the importance of managerial skills - Dibie, Robert; Herron, Sharron Y. (2002)
This study analyzes Nigerian public managers' perception of the importance of managerial skills and management principles. The study presents an argument that national and state governments in Nigeria should use management principles to "steer, not row" their respective societies. It outlines some of the major steps required to create a dynamic public management and governmental machinery capable of both planning and execution of comprehensive development plans in the future. The study addresses the question: How can Nigeria's government extract management resources from its society and deploy them to create and support a cohesive and public management in Nigeria needs to be reformed to play a more developmental and accountable role in the future. New public management principles are also utilized in evaluating how the reform can be accomplished. - Reproduced.
Keywords: Management techniques; Public administration